2020
DOI: 10.1080/14680777.2020.1856908
|View full text |Cite
|
Sign up to set email alerts
|

“I can’t believe your mixed ass wasn’t on the pill!”: race and abortion on American scripted television, 2008-2019

Abstract: Racial identities provide important context for understanding reproductive experiences, including abortion. However, this context is often not fully reflected in popular cultural narratives about abortion, including on American television. Because onscreen depictions have the potential to influence public understandings of abortion, it is crucial to examine the messages these plotlines convey about the relationship between race, racism, and abortion access. We analyze a decade of onscreen abortion depictions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…In support of the literature on Black-Asian racial stereotypes (Herold et al 2020;Washington 2015Washington , 2017a, we find that Black-Asian men and women Redditors described encounters where monoracial White, Black and Asian acquaintances, classmates, friends, and family members projected racialized, gendered, and hypersexualized stereotypes towards their multiracial identity. Our analysis indicates that Black-Asian users, particularly men, overwhelmingly discussed navigating stereotypes of their Black heritage as strong, masculine, hypersexual, ignorant, and deviant compared with their Asian heritage as weak, feminine, and submissive.…”
Section: Microaggressions Based On Racial Stereotypessupporting
confidence: 79%
See 4 more Smart Citations
“…In support of the literature on Black-Asian racial stereotypes (Herold et al 2020;Washington 2015Washington , 2017a, we find that Black-Asian men and women Redditors described encounters where monoracial White, Black and Asian acquaintances, classmates, friends, and family members projected racialized, gendered, and hypersexualized stereotypes towards their multiracial identity. Our analysis indicates that Black-Asian users, particularly men, overwhelmingly discussed navigating stereotypes of their Black heritage as strong, masculine, hypersexual, ignorant, and deviant compared with their Asian heritage as weak, feminine, and submissive.…”
Section: Microaggressions Based On Racial Stereotypessupporting
confidence: 79%
“…Their findings suggest that popular culture stereotypes Black-Asian womanhood as hyper-sexual, parallel to the "jezebel" controlling image stereotype of monoracial Black women (Hill Collins 2000) or the purity stereotype of monoracial Asian women (Chou 2012;Herold et al 2020). For illustration, Herold et al (2020) find that multiracial Black-Asian women are depicted as simply "displaying" sexuality, whereas monoracial Black women are shown to "deploy" theirs. Furthermore, in a review of media coverage on Tiger Woods, Washington (2015) found that the professional golf player navigates both Black racial stereotypes, such as "hyper-sexuality", "hyper-aggression", and "criminality", and Asian stereotypes such as "bad-driver", and "femininity".…”
Section: Pathologizing Of Identity and Experiencesmentioning
confidence: 99%
See 3 more Smart Citations